Women as "gold dust": Gender diversity in top boards and the performance of Italian banks. (29th December 2020) - Del Prete, Silvia; Stefani, Maria Lucia
Abstract: This paper investigates the effects on riskiness and performance of gender diversity in Italian bank boards. Italy deserves special attention because European comparisons for the 2000s show that it was among the European Union countries where women were least represented in bank boardrooms, and this gap remains even in a quota law regime. Our main econometric results suggest that gender diversity may have a positive impact on the credit portfolio riskiness and on profitability. Both results may be driven by women's higher risk aversion and their higher propensity to monitor activities, suggesting that women are "gold dust" for Italian banks. These findings, obtained by using a unique data set over the period 1995–2010 and by taking into account possible sources of endogeneity, support the effectiveness on bank performance of greater female presence on boards. Moreover, our econometric set‐up could offer a benchmark for further analysis on gender diversity effects for many countries, where a gender quota law is still not in place.